Interaktivitetsbegreber - Rosendal Nielsen, Thomas (Peripeti, 2021)
Nielsen presents a range of interactivity definitions from the areas of communication and media studies and discusses their heuristic implications for a dramaturgical thinking of interactivity. In conclusion, Nielsen suggests a basic definition of interactivity from the perspective of systems theory.